Outcomes of drug-eluting and bare metal stents in saphenous vein graft percutaneous coronary intervention: a single centre experience. (22nd September 2015) - Nair, SB; Eichofer, J; Clarke, B; El-Omar, M; Fath-Ordoubadi, F; Fraser, D; Khattar, RS; Neyses, L; Mamas, M
Abstract : Introduction: Both large randomised multicentre trials and registry studies have demonstrated that percutaneous coronary intervention (PCI) with drug-eluting stents (DES) is associated with reduced restenosis and major adverse cardiac event (MACE) rates compared with bare metal stents (BMS) in native coronary arteries. Despite this large body of evidence for lesions in native coronary arteries, lesions in saphenous vein grafts (SVG) have either been excluded or poorly represented from pivotal DES trials. The optimal PCI treatment of SVG remains unknown despite SVG interventions representing up to 10–15% of PCI cases in many centres. Diseased SVG often contain large, soft friable lesions consisting of necrotic debris, inflammatory cells and thrombus, thus raising concerns regarding the use of DES for these lesions. In the recent randomised DELAYED RRISC trial (Vermeersch et al, JACC 2007) sirolimus-eluting stents were associated with a greater mortality than BMS for SVG disease. Methods: We retrospectively studied 388 consecutive patients admitted to Manchester Heart Centre for PCI to SVG lesions from August 2001 to August 2008 with mean follow-up time 41.9 ± 23.5 months (median 41.5 months) in the largest registry series to our knowledge to date to determine outcomes in BMS and DES in SVG intervention cases. The primary endpoint was defined as total mortality and the secondary endpoint was MACE defined as composite endpoint of death, stroke, myocardial infarction, stent thrombosis and target lesion/vessel revascularisation. Results: Of the 388 patients studied, a total of 219 patients had BMS and 169 had DES implanted; the demographics are presented in table 1. Lesion and vessel characteristics are presented in table 2. Over the period studied there was a total of 13/169 deaths in the DES group (7.7%) and 30/219 in the BMS group (14.7%) p<0.05. However, 1-year mortality rates were 4.0% and 6.0% in the DES and BMS groups, respectively (p = NS). MACE was observed in 50/169 (29.5%) in the DES group and 80/219 (36.5%) in the BMS group (p = NS). One-year MACE rates were 12.3% and 11.6% in the DES and BMS groups, respectively (p = NS). Conclusion: In the largest registry series to date with the longest mean follow-up period to our knowledge we have demonstrated a greater mortality in patients receiving BMS compared with DES during SVG PCI, despite a greater proportion of patients with diabetes and smaller mean stent diameter in the DES group, which would tend to effect outcomes adversely. These observations are in contrast to the findings of the recent randomised DELAYED RRISC trial containing 75 patients, in which an adverse outcome was associated with DES use in SVG cases. DES in SVG PCI is safe and is not associated with an excess mortality risk compared with BMS in the single centre cohort that we have studied.